If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2x + -3 + 4y) = 0 Reorder the terms: -1(-3 + 2x + 4y) = 0 (-3 * -1 + 2x * -1 + 4y * -1) = 0 (3 + -2x + -4y) = 0 Solving 3 + -2x + -4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -2x + -3 + -4y = 0 + -3 Reorder the terms: 3 + -3 + -2x + -4y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x + -4y = 0 + -3 -2x + -4y = 0 + -3 Combine like terms: 0 + -3 = -3 -2x + -4y = -3 Add '4y' to each side of the equation. -2x + -4y + 4y = -3 + 4y Combine like terms: -4y + 4y = 0 -2x + 0 = -3 + 4y -2x = -3 + 4y Divide each side by '-2'. x = 1.5 + -2y Simplifying x = 1.5 + -2y
| -1/5(x-15)-1/9(x-9)=x-3 | | 24x-48=3x^2 | | N^3-4n=32 | | 2/5n-1=15 | | -5x-248=92-15x | | 4(3)x+2=28 | | y=x^11 | | x^3+6x^2+9x=-5 | | (14)(2)+2x+32=70 | | 4lnx-7=1 | | -4(x+4)-2=-18 | | -0.5*32x^2+24x+50=0 | | x^3+6x^2+9x=5 | | 10x+1=2x+73 | | (-1+i)-(-2-i)=0 | | -50+8x=5x+52 | | x^3+3x^2-3x=0 | | (5x+10)+7x= | | -3(x-4)+4=-4(3x-3)+6+13x | | 16m=76 | | 2x-5y=-25 | | 4(3x+8)=80 | | 6(5x+11)-9x= | | 35=-7+3n | | 23n-24n= | | 2=15x^2+x | | y=0.13x+585 | | 4(3n+3)=9(9n+1)+5 | | (x-(8/x))^2-5(x-(8/x))-14=0 | | 12x-127=4x+169 | | (8x^4-2x^2+3x-5)-(2x^4+x^3+3x+5)= | | (3x+3)+(15-3x)= |